To the Problem of Humanization of Relations of Teenagers Who are Brought up in a Family Environment, with Children from Orphanages - Ionova, Iryna (Pedagogical Discourse, 2017)
In the article the author analyzes the definition of humanization of relations of teenagers who are brought up in a family environment, with children from orphanages. Define the concept of «humanism», «humanity», «the humanization of relations», «socio-pedagogical project activity». Clarified the essence of the concept «humanization of relations». The humanization of relations between people is seen as a process of humanization of communication on the basis of subject-subject interaction of equal partners, the recognition of everyone’s right to be a person, to freely exercise their choice and will. It is noticed that as the bilateral process of humanization of the relationship involves collaboration and co-creation, creating conditions for their self-development the approval of personal dignity. The result of humanized relationships is humanized (humane) personality of the pupil. Defined the peculiarities of adolescence and the role of communication. The attention is focused on the fact that inadequate self – esteem of teenagers, their heightened emotional tension and anxiety, incompleteness of communication skills often lead to aggressive behavior, negativity, defiant behavior, manifestations of cruelty. The features of the social development of children from orphanages. It is noticed that the process of assimilation of orphaned children and children deprived of parental care, a particular system of knowledge, norms and values, due to the shortcomings of education in the same families (neglect, maltreatment and the like) and the effects of imperfect system of education in orphanages facilities (material conditions and means of life, inadequate communication with adults, the lack of contacts with the environment, narrow circle of communication, the regulation of free time sensitive moments). Reviewed the content of project activities and the activities of entities of project activities. Investigated the possibilities of social and educational projects as a means of humanization of the relations of the adolescents brought up in a family environment, with children from orphanages.